2017
DOI: 10.3892/etm.2017.5585
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of C‑X‑C motif chemokine 10 reduces graft loss mediated by memory CD8+ T cells in a rat cardiac re‑transplant model

Abstract: Abstract. The interaction of chemokine (C-X-C motif) ligand 10 (CXCL10) with its receptor (CXCR3) is a critical process in recruiting donor reactive T cells to a graft and alloantigen-specific memory T (Tm) cells exert a principal function in promoting graft dysfunction during accelerated cardiac rejection. However, whether CXCL10 chemokine exerts any effects on acute accelerated rejection mediated by CD8 + Tm cells in a re-transplant model has remained elusive. The present study established a cardiac transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Previous studies have shown that the CXCL9 and CXCL10 genes' over-expression was associated with rejection processes, regardless of the tissue's type of rejection and origin (3,31,32). In heart transplant models, CXCL10 inhibition slows rejection and increases graft survival (33) The data from our analyzes confirm those obtained by other researchers, showing that the ligands that regulate the activation of the CXCR3 receptor are a potential biomarker and therapeutic target. In addition, among the over-expressed genes, we also obtained other biological pathways unrelated to transplantation, such as infection by Leishmaniasis and Staphylococcus aureus.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that the CXCL9 and CXCL10 genes' over-expression was associated with rejection processes, regardless of the tissue's type of rejection and origin (3,31,32). In heart transplant models, CXCL10 inhibition slows rejection and increases graft survival (33) The data from our analyzes confirm those obtained by other researchers, showing that the ligands that regulate the activation of the CXCR3 receptor are a potential biomarker and therapeutic target. In addition, among the over-expressed genes, we also obtained other biological pathways unrelated to transplantation, such as infection by Leishmaniasis and Staphylococcus aureus.…”
Section: Discussionsupporting
confidence: 86%